Sarconesin II, a New Antimicrobial Peptide Isolated from Sarconesiopsis magellanica Excretions and Secretions (2019)
Antibiotic resistance is at dangerous levels and increasing worldwide. The search for new antimicrobial drugs to counteract this problem is a priority for health institutions and organizations, both globally and in individual countries. Sarconesiopsis magellanica blowfly larval excretions and secretions (ES) are an important source for isolating antimicrobial peptides (AMPs). This study aims to identify and characterize a new S. magellanica AMP. RP-HPLC was used to fractionate ES, using C18 columns, and their antimicrobial activity was evaluated. The peptide sequence of the fraction collected at 43.7 min was determined by mass spectrometry (MS). Fluorescence and electronic microscopy were used to evaluate the mechanism of action. Toxicity was tested on HeLa cells and human erythrocytes; physicochemical properties were evaluated. The molecule in the ES was characterized as sarconesin II and it showed activity against Gram-negative (Escherichia coli MG1655, Pseudomonas aeruginosa ATCC 27853, P. aeruginosa PA14) and Gram-positive (Staphylococcus aureus ATCC 29213, Micrococcus luteus A270) bacteria. The lowest minimum inhibitory concentration obtained was 1.9 µM for M. luteus A270; the AMP had no toxicity in any cells tested here and its action in bacterial membrane and DNA was confirmed. Sarconesin II was documented as a conserved domain of the ATP synthase protein belonging to the Fli-1 superfamily. The data reported here indicated that peptides could be alternative therapeutic candidates for use in infections against Gram-negative and Gram-positive bacteria and eventually as a new resource of compounds for combating multidrug-resistant bacteria. © 2019 by the authors.